The Effect of Health Education on Gastritis Prevention Behavior Among High School Students - Muhammad Taufan Umasugi; Fathmy F Soulissa; Inta Susanti; Grolya R Latuperissa (Jurnal Ners, 2020)
Introduction: Gastritis is the inflammation of the gastric mucosa that is characterized by discomfort felt in the upper abdomen in addition to nausea, vomiting, a decreased appetite and headaches.  The purpose of this study was to determine the effect of health education on the student’s behavior and on the prevention of gastritis. Methods: The design used was pre-experimental with a pretest-posttest design approach. The sampling technique used in this study was a total sampling technique resulting in 57 respondents. Before the intervention, the respondents filled in a questionnaire about the concept of gastritis. Furthermore, the respondents were given health education intervention material about gastritis in the form of leaflets containing information on the understanding, causes, signs and symptoms, risk factors and prevention. The intervention was only conducted for one session for 20-30 minutes per respondent. Following this, 1 hour later, the intervention was evaluated by giving the same questionnaire to the respondent to fill in according to the questions. The data analysis used a paired sample t-test ρ = 0,000.Results: The results showed an increase in behavior before and after the intervention related to preventing gastritis among the students. The results showed that 28 respondents (49.1%) with good behavior changed to 33 respondents (57.9%) who behaved well. Conclusion: The conclusion is that there is a significant influence from counseling on the prevention of gastritis among high school students.